Color tunable single-phase Eu2+ and Ce3+ co-activated Sr2LiAlO4 phosphors. Issue 25 (5th June 2019) - Ha, Jungmin; Kim, Yoon Hwa; Novitskaya, Ekaterina; Wang, Zhenbin; Sanchez, Maritza; Graeve, Olivia A.; Ong, Shyue Ping; Im, Won Bin; McKittrick, Joanna
Abstract : Color tunable single-phase phosphors (blue- to green-emitting) were fabricated with co-activators that also improved the quantum efficiency. Abstract : High purity Eu 2+ and Ce 3+ singly and co-activated Sr2 LiAlO4 phosphors were successfully synthesized through a facile combustion reaction. Fabrication of color tunable, single-phase phosphors was achieved by varying the Eu 2+ /Ce 3+ ratio that utilized the energy transfer between Ce 3+ and Eu 2+ . For the singly activated compositions, the highest quantum efficiencies were 25% and 40% for Sr1.998 Eu0.002 LiAlO4 and Sr1.998 Ce0.002 LiAlO4, respectively. The emission of Sr2 LiAlO4 :Ce 3+ and the excitation of Sr2 LiAlO4 :Eu 2+ overlap in the range of 400 nm–500 nm, so that energy transfer from Ce 3+ → Eu 2+ takes place. The emission color of Eu 2+ and Ce 3+ co-activated Sr2 LiAlO4 changes from blue, to cool-white, to green depending on the activator concentrations. The maximum quantum efficiency of Eu 2+ and Ce 3+ co-activated Sr2 LiAlO4 was 55%, a 40% increase over the singly activated phosphors, which demonstrates that the quantum efficiency improves by co-activation.